BUILDING A STRATEGY FOR THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES IN SOUTH SULAWESI - Rahman, Zainuddin (Journal of Humanity, 2015)
The research was to understand the purpose of understanding of the authorities, banking, and abuser of Small Medium Enterprises (UMKM). Business organizations, community leaders, in the building of UMKM development strategy. This research approach is qualitative by the method of Phenomenology of approach by understanding the perspectives of ethics within the emic and interpret the disclosure of informants involved in this research. The unit of analysis in this research are: Individual businessmen of UMKM in the fields of food and beverage industry, individual government officials from the Department of industry, cooperatives and regional SME research, Individual figures of Individual regions, the Business Banking Officials, individuals representing community leaders who understand the problem of UMKM. The data collection methods used are: observation, in-depth Interviews, and documentation. The research instruments the researcher as the main instrument. Research findings is that for member access to capital, access technology, and the market for UMKM, the Government must establish a credit guarantee institutions, build partnerships with banks, State-Owned Enterprises, BUMB, large companies, Commerce, cooperatives, universities and NGOs. In addition to the members access for marketing, the Government should establish a joint marketing Center for UMKM in the form of an outlet. favor and absolute protection against UMKM so that the Government can develop on an ongoing basis from time to time. To develop UMKM continuously especially for UMKM engaged in the food industry, the Government should build the development strategies in the form of partnerships between large and UMKM entrepreneurs with all stakeholders in the area of South Sulawesi.